Starches in Rice: Effects of Rice Variety and Processing/Cooking Methods on Their Glycemic Index - Muhammad Adil Farooq; Jianmei Yu (Foods)
Rice is a fundamental food source for more than fifty percent of the world’s population, significantly contributing to human nutrition and food security. Like other cereal grains, rice is rich in starch, although it also contains protein, vitamins, and minerals. Regular consumption of white rice has been reported to be positively associated with the increased risk of type 2 diabetes in rice-consuming countries due to the high glycemic index (GI) of white rice. However, the nutritional value and health effects of rice differ markedly depending on the variety and are influenced by processing methods, cooking styles employed, and the presence of other food components/ingredients. Therefore, this review examines the chemical compositions, starch structures, and glycemic indices of different rice types and the impact of processing techniques and genetic mutation on starch’s structure, amylose content, and GI. The interactions between rice starch and other food components, such as proteins, lipids, dietary fibers, and polyphenols, and their impact on the digestibility and GI of rice starch are also discussed. The purpose of this comprehensive review is to elucidate the strategies that can improve the nutritional advantages of rice and mitigate health issues, such as obesity, diabetes, and inflammation, linked to the long-term consumption of rice.